Implications of Curriculum in Promoting Critical Thinking, Creativity and Innovation Among Learners - Adhikari, Sapana; Sigdel, Surya; Shrestha, Suman Kumar; Basnet, Hom Bahadur (Education and Development, 2025)
Transforming the education system to enhance creativity and innovation is essential for equipping students to succeed in an increasingly complex and dynamic world. Contrarily, traditional education models often focus on rote memorization and standardized testing, which can hinder creativity and limit critical thinking. This paper examines the impact of the basic-level curriculum on fostering critical thinking, creativity, and innovation among students in Nepal. It also considers the influence of the traditional top-down educational model and the efforts to promote learner-centered, creativity-oriented, and contemporary educational practices. To achieve these ends, a qualitative case study approach, specifically the narrative inquiry design, was utilized to investigate how curriculum design and instructional practices affect the development of 21st-century competencies in secondary schools. The data were collected through in-depth interviews, observations, and online communications with students, teachers, and administrators from three community basic-level schools in Chandragiri Municipality. The results reflect ongoing educational activities that remain traditional, teacher-centered, and rote-learning-oriented, relying on paper-and-pencil methods. The strategies employed to enhance critical thinking, creative work, and innovative performance, and to provide students with hands-on experiences, are weak and insufficiently emphasized. The study recommends that traditional curricula must be updated to equip students with 21st-century skills.